Project Report on Design and Development of PC Interface Mobile Operating - GEETHA PRIYA, PRABHAVATHI, VINUTHA and YAMINI THOMAS (1999)
INTERNAL GUIDE:D CHANDRASHEKAR,MVJCE
Keywords: Design and Development of PC Interface Mobile Operating